Caregiver Strategies to Sensory Features for Children With Autism and Developmental Disabilities - Little, Lauren M.; Ausderau, Karla; Freuler, Ashley; Sideris, John; Baranek, Grace T. (Frontiers in Psychology, 2022)
Background. Caregivers of children with autism spectrum disorders (ASD) and developmental disabilities (DD) implement myriad strategies to support their children during daily activities and routines, which are laden with sensory stimuli. Children’s sensory features are often characterized by three patterns of response (i.e., hyperresponsiveness, hyporesponsiveness, sensory seeking), and little is known about how caregivers’ strategies differ among these patterns. Therefore, we used a mixed methods analysis to examine the complex interplay between children’s sensory response patterns, child characteristics (diagnosis, chronological age, mental age), and caregiver strategies. Specifically, we examined how children’s sensory response patterns were associated with caregiver strategies within sensory response pattern and at the item level. Lastly, we described the differential strategies implemented by caregivers of children with ASD and DD by sensory response pattern. Methods. Participants included children with ASD (n=77) and DD (n=40) aged 2-10 years. Caregivers completed the Sensory Experiences Questionnaire-2.1. A convergent parallel mixed methods approach was used to analyze data. Results. Children’s sensory response pattern scores were significantly, positively associated with caregiver strategies within each sensory pattern (hyperresponsiveness, hyporesponsiveness, seeking); however, child mental age, and chronological age were not significantly related to the rate of caregiver strategies across patterns. While caregivers of children with ASD reported an using more strategies, child diagnosis did not moderate the association between child sensory response pattern scores and the rate of caregiver strategies used. Item analysis demonstrated specific child behaviors in response to sensory stimuli that elicited high rates of strategies among caregivers. Qualitative analysis revealed distinct themes characterized caregiver strategies within each sensory pattern for children with ASD and DD. Conclusion. Our findings demonstrated specificity of caregiver strategies to children’s sensory response patterns in the context of families’ everyday lives, which were not contingent on child diagnosis, mental age, or chronological age, thereby highlighting universal qualities of caregiving for young children who experience varying levels of sensory challenges. Targeted intervention approaches may differentially incorporate types of strategies based on sensory response patterns to more optimally facilitate children’s activity participation.